The Role of Computer Technologies in Structuring Evidence Gathering in Cybercrime Investigations: A Qualitative Analysis - Steinmetz, Kevin F. (Criminal justice review, 2025)
In recent decades, law enforcement agencies have increasingly prioritized cybercrime investigations, as evinced by the growing adoption of specialized cybercrime units and personnel. A burgeoning literature has emerged which examines cybercrime units and investigators. Yet, little attention has been given to the role of computers in shaping these investigations. This study addresses this gap through an analysis of qualitative interviews with 47 cybercrime investigative personnel including sworn detectives, civilian analysts, and unit administrators. This analysis confirms and extends prior research by exploring challenges presented by computers to cybercrime investigations including issues surrounding anonymization, encryption, jurisdiction, caseloads, backlogs, data volume, eliciting data from electronic service providers, and the ever-changing technological landscape. Also considered are the advantages offered by such technologies for cybercrime investigations. Computer and network technologies facilitate undercover investigations, provide easy access to global networks and databases, and supply large quantities of evidence to help secure convictions. Finally, this study considers elements of cybercrime investigations not supplanted by computer databases, automation, or network systems. Directions for future research and policy implications are considered.